PENEGAKAN HUKUM KEPADA PELAKU TINDAK PIDANA PERSETUBUHAN TERHADAP ANAK DI WILAYAH HUKUM POLRES BULELENG - Anggara, Bayu; Tololiu, Yudi Gabriel (Kerta Dyatmika, 2023)
The criminal offense of sexual intercourse with minors constitutes a serious societal issue, often resulting from the perpetrator’s failure to exercise rational judgment, driven instead by uncontrollable lust. The increasing frequency of such offenses in Indonesia is influenced by multiple factors, including technological advancement, which, while beneficial, also facilitates criminal activity. This research aims to examine the enforcement of legal measures against perpetrators of child sexual offenses and to analyze the countermeasures undertaken by the Buleleng District Police (Polres Buleleng). The study employs an empirical legal research method. The findings indicate that effective law enforcement requires collaborative efforts across various sectors, and that crime prevention efforts by the police must be enhanced. Preventive strategies should target the general public, individuals with potential to commit crimes, and those who have previously committed criminal acts. The study concludes that community supervision plays a crucial role in preventing child sexual crimes, and that comprehensive support is needed from all components of the criminal justice system, including contributions from the social, economic, and public policy sectors, particularly within the jurisdiction of the Buleleng District Police.